Economic growth new directions in theory and policy - Arestis Philip; Baddeley Michelle; McCombie John S L (Cheltenham Edward Elgar, 2007)
This volume focuses on the nature, causes and features of economic growth across a wide range of countries and regions. Covering a variety of growth related topics - from theoretical analyses of economic growth in general to empirical analyses of growth
Keywords: Economic development; Economic growth